Assessment of Prescribing Indicators in Public and Private Primary Healthcare Facilities in Java Island, Indonesia - Yuniar, Yuyun; Susyanty, Andi Leny; Sari, Ida Diana (Jurnal Kefarmasian Indonesia, 2017)
Prescribing indicator is an easy core indicator to evaluate drug utilization as stated in WHO guideline. Rational prescribing pattern is important to improve rational use of drugs whereas irrational prescribing pattern can lead to irrational drug use. This study aimed to assess the prescribing pattern in public and private primary healthcare facilities which were included in the National Health Insurance Program in Indonesia. This study has been conducted using the cross sectional research design, quantitative and retrospective method in four provinces in Java island (West Java, Banten, DIY and Central Java provinces) from May to July 2014. The method of retrospective data collection were collected 757 prescriptions from 26 PHCs and 900 prescriptions from 30 clinics or General Practitioners (GPs). All data in the prescribing form were analyzed manually using Microsoft Excel 2007. The average number of item in public and private facilities was 3.31 and 3.06 respectively. The percentage of generic prescribing was 93.3% and 62.0%, the percentage of drugs in accordance with the 2013 national formulary was 89.0% and 64.5%, the percentage of antibiotic per total number of encounter was 42.8% and 39.4%, while the percentage of injection per total encounter was only 0.7% and 2.2%. Paracetamol and dexamethasone were the most frequently prescribed drugs while for antibiotic group were amoxicillin, ciprofloxacin, cotrimoxazole and cefadroxil.The average number of items per encounter and antibiotic were not met the WHO standard(≤3 for average number and less than 30% for antibiotic percentage). Suitable interventions are needed to improve the prescribing practices in Indonesia